Wine Microbiology Practical Applications and Procedures - Fugelsang, Kenneth C.; Edwards, Charles G. (Springer US : Imprint: Springer, 2007)
Since publication of the first edition of Wine Microbiology in 1997, the volume of new information and concepts has dramatically increased. Even with the tremendous increase in available information, a comprehensive understanding regarding the role of individual microorganisms towards wine quality as well as the impact of complicated interactions between microorganisms and processing techniques is lacking. Wine Microbiology, Second Edition, fills this void. Like the first edition, the book addresses real world problems such as characterization and enumeration of yeast, bacteria and molds common to juice and wine environments and their impact on wine quality and stability. In addition, the potential of solving processing problems through rapid, real-time molecular methods and new applications for using starter cultures of non-Saccharomyces yeast are discussed. The book is a great resource for professionals and students in the field of enology and viticulture. About the Authors: Kenneth C. Fugelsang has been associated with California State University (Fresno) since 1970 and is now wine master and professor of enology. He is an author of 12 books and over 100 technical papers and presentations. Charles G. Edwards has been a professor with the Department of Food Science and Human Nutrition at Washington State University since 1989. He has authored over 150 technical papers and presentations and is author of the book Illustrated Guide to Microbes and Sediments in Wine, Beer, and Juice.